Muscular Adaptations to Whole Body Blood Flow Restriction Training and Detraining - Brandner, Christopher R.; Clarkson, Matthew J.; Kidgell, Dawson J.; Warmington, Stuart A. (Frontiers in Physiology, 2019)
Resistance training with blood flow restriction is typically performed during single exercises for the lower- or upper-body, which may not replicate real world programming. The present study examined the change in muscle strength and mass in a young healthy population during an 8-week whole body resistance training program, as well as monitoring these adaptations following a 4-week detraining period. Thirty-nine participants (27 males, 12 females) were allocated into four groups: blood flow restriction training (BFR-T); moderate-heavy load training (HL-T), light-load training (LL-T) or a non-exercise control (CON). Testing measurements were taken at Baseline, during mid-point of training (week 4), end of training (week 8) and following four weeks of de-training (week 12) and included anthropometrics, body composition, muscle thickness at seven sites, and maximal dynamic strength (1RM) for six resistance exercises. Whole body resistance training with BFR significantly improved lower- and upper-body strength (overall; 11% increase in total tonnage), however this was similar to LL-T (12%), but both groups were lower in comparison with HL-T (21%) and all groups greater than CON. Some markers of body composition (e.g. lean mass) and muscle thickness significantly increased over the course of the 8-week training period, but these were similar across all groups. Following de-training, whole body strength remained significantly elevated for both BFR-T (6%) and HL-T (14%), but only the HL-T group remained higher than all other groups. Overall, whole body resistance training with blood flow restriction was shown to be an effective training mode to increase muscular strength and mass. However, traditional moderate-heavy load resistance training resulted in greater adaptations in muscle strength and mass as well as higher levels of strength maintenance following detraining.